The Effect of Local Taxes, Capital Expenditure, Investment, and Labour Force on Local Revenue with Economic Growth as an Intervening Variable - Nanda Pinandita Ramadhani; Mulyanto Nugroho; Nekky Rahmiyati (International Journal of Economics Accounting and Management, 2025)
This research aims to analyse the effect of local taxes, capital expenditure, investment, and labour force on local revenue with economic growth as an intervening variable in the regency / city in the Eks Karesidenan Pekalongan region year 2018-2023. The approach used is quantitative, using the Structural Equation Modeling (SEM) analysis method based Partial Least Square (PLS). The data analysed is secondary data obtained from the Central Statistics Agency (BPS) and related agencies. The research sample consists of all districts/cities in the Eks Karesidenan Pekalongan Central Java area with a six-year observation period. The results show that local taxes, capital expenditure, and labor force have a significant influence on economic growth, but only local taxes have a significant effect on local revenue. In contrast, investment do not show a significantly effect on economic growth or local revenue. Economic growth also has no significant effect on own-source revenues. Furthermore, the intervening variable of economic growth cannot mediate the relationship between local taxes, capital expenditure, investment, and labour force on local revenue. These findings indicate the need to optimise local tax and capital expenditure management strategies to increase local revenue. In addition, local governments need to pay attention to other factors beyond investment and labour force that can contribute to local revenue and economic growth in a sustainable manner